ANALYSIS OF LANDSCAPE ELEMENTS THAT AFFECT PROPERTY VALUE BASED ON THE PERCEPTION OF HOUSING RESIDENTS IN SURABAYA - Wibisono, Nita Setiawati; Kwanda, Timoticin; Anastasia, Njo (DIMENSI (Journal of Architecture and Built Environment), 2017)
This research is done to determine landscape elements that affect property value based on housing residents’ perception in Surabaya residential areas. The landscape elements that used in this research are natural elements such as vegetation and soil; and man-made element such as garden statue, road pattern, road width and hierarchy, park and plant, artificial lake, and road equipment. Purposive sampling technique is used to represent respondents in the residential areas that provide landscape elements in East and West Surabaya. Data analysis technique uses validity and reliability test, analysis factor, binary logistic regression, and the average of variable test. The result shows that majority of the residents of East Surabaya and West Surabaya residential areas approved that landscape consist of park and plant, road width and hierarchies, and road pattern affect their residential property values. The residents are also willing to contribute about 7.4% of their house price to improve the appearance of the residential landscape.